P1_6 The Revenge of Pluto - Holt, Nicholas; Roberts, Kieran; Murphy, Jeremy; Tranter, Jemima (Physics Special Topics, 2020)
Pluto is a bit annoyed at being demoted to a dwarf planet, and it is after revenge. It plans to collide with and destroy the Earth by adjusting its own orbit. In this paper, the minimum value for the velocity of Pluto (relative to the Earth) will be calculated, in order for it to destroy the Earth, as well as the minimum separation between the two bodies at which if the system was released from a stationary state, gravitational forces would cause the acceleration of the bodies, and so, destruction.